Shaping Business Managers’ English in BBA (Journal of Management, 2020)
This article analyses how the current course of English in Bachelor of Business Administration (BBA) in Tribhuvan University has used interdisciplinary approach in teaching English for business communication to would-be business administrators. To prepare the background and methodology of the analysis, the history of such courses in the global context is reviewed and certain parameters are devised based on B.F. Skinner’s theory of language shaping. It is found that the course has maintained the international standard and so is appropriate for aspiring business managers. The integration of language, literature, technical writing skills and business management related contents has made the course useful and difficult to handle at the same time. Active and motivated participants of both the course instructor and the learners is necessary to make the course successful with the achievement of the objectives the curriculum devised.